Assessing the Relation between Organization Climate and Job Nature with Staffs’ Job Motivation in Isfahan Hospitals (بیمارستان, 2015)
Background: Staffs’ Job motivation is one of the most important factors in goals achievement in organization. As a result, considering effective factors of staffs’ motivation is one of the main tasks of organization managers. The aim of current study is to assess the relation between organization climate and job nature with staffs’ job motivation in Isfahan hospitals.